A synthetic sex ratio distortion system for the control of the human malaria mosquito - Galizi,R; Doyle,LA; Menichelli,M; Bernardini,F; Deredec,A; Burt,A; Stoddard,BL; Windbichler,N; Crisanti,A (Nature Communications, 2014)
It has been theorized that inducing extreme reproductive sex ratios could be a method to suppress or eliminate pest populations. Limited knowledge about the genetic makeup and mode of action of naturally occurring sex distorters and the prevalence of co-evolving suppressors has hampered their use for control. Here we generate a synthetic sex distortion system by exploiting the specificity of the homing endonuclease I-PpoI, which is able to selectively cleave ribosomal gene sequences of the malaria vector Anopheles gambiae that are located exclusively on the mosquito’s X chromosome. We combine structure-based protein engineering and molecular genetics to restrict the activity of the potentially toxic endonuclease to spermatogenesis. Shredding of the paternal X chromosome prevents it from being transmitted to the next generation, resulting in fully fertile mosquito strains that produce >95% male offspring. We demonstrate that distorter male mosquitoes can efficiently suppress caged wild-type mosquito populations, providing the foundation for a new class of genetic vector control strategies.